Determinants adoption of computer assisted auditing tools (CAATs) - Pedrosa, I.; Costa, C.; Aparicio, M. (Cognition, Technology and Work, 2020)
During the last fifteen years, several studies on technology acceptance have been pursued, and several new models have been proposed. This paper presents a theoretical background on individual acceptance of Computer-assisted Audit Tools (CAATs) in the context of statutory auditors of a European country. The adoption of technologies in auditing is considered an important factor for efficiency increasing and effectiveness of auditing work. This study identifies the adoption determinants of CAATs; and develops a CAATs, adoption model. Quantitative research was carried out and operationalized by a survey to statutory auditors. Findings indicate that the perceived usefulness of CAATs, the effort expectancy, the facilitating conditions, and the number of auditors are the main drivers of the adoption and use of CAATs. This research presents significant contributions impacting the various stakeholders: Statutory Auditors, Statutory Auditors Firms, Institutes of Statutory Auditors, and Academy.